2006
DOI: 10.1074/jbc.m512917200
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphotyrosine Peptide Binding Specificity of Nck1 and Nck2 Src Homology 2 Domains

Abstract: Nck proteins are essential Src homology (SH) 2 and SH3 domain-bearing adapters that modulate actin cytoskeleton dynamics by linking proline-rich effector molecules to tyrosine kinases or phosphorylated signaling intermediates. Two mammalian pathogens, enteropathogenic Escherichia coli and vaccinia virus, exploit Nck as part of their infection strategy. Conflicting data indicate potential differences in the recognition specificities of the SH2 domains of the isoproteins Nck1 (Nck␣) and Nck2 (Nck␤ and Grb4). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 54 publications
4
92
1
Order By: Relevance
“…It has been reported that Tyr392 of Git1 can be phosphorylated and that this phosphorylation enables its binding to the SH2 domain of Nck (Frese et al, 2006). We however found that mutation of Tyr392 into phenylalanine (Git1Y392F-FLAG) does not affect its complex formation with EphA2-HA ( Figure 6D).…”
Section: Precise Mechanisms Of Formation Of the Epha2-nck1-git1 Complexmentioning
confidence: 42%
See 1 more Smart Citation
“…It has been reported that Tyr392 of Git1 can be phosphorylated and that this phosphorylation enables its binding to the SH2 domain of Nck (Frese et al, 2006). We however found that mutation of Tyr392 into phenylalanine (Git1Y392F-FLAG) does not affect its complex formation with EphA2-HA ( Figure 6D).…”
Section: Precise Mechanisms Of Formation Of the Epha2-nck1-git1 Complexmentioning
confidence: 42%
“…In contrast, Git1 has been shown to bind to several adaptor proteins, such as Nck (Frese et al, 2006). Among the Nck isoforms, MDCK cells predominantly express Nck1 (Supplemental Figure S1).…”
Section: Epha2 Requires Nck1 To Associate With Git1mentioning
confidence: 99%
“…Nck1 and Nck2 display 68% identity at the amino acid level and are regarded to be functionally redundant in many aspects although some Nck1-or Nck2-specific interactions/functions have been reported (reviewed in [2]). Nonetheless, binding specificities of the isolated SH2 domains of Nck1 and Nck2 are nearly the same and both recognize a YDEV consensus-binding sequence [35]. Although both Y 378 (YEDV) and Y 397 (YEEV) of HS1 closely resemble this consensus motif, Nck specifically binds to phosphorylated Y 378 but not to Y 397 .…”
Section: Discussionmentioning
confidence: 99%
“…Although both Y 378 (YEDV) and Y 397 (YEEV) of HS1 closely resemble this consensus motif, Nck specifically binds to phosphorylated Y 378 but not to Y 397 . This specificity might rely on a leucine residue in the +4 position of Y 397 , since it has been reported to be disfavored in this position and to impair Nck SH2 domain binding [35]. In contrast the Y 378 motif harbors a glutamic acid in the +4 position that is rather tolerated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation